The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1108/00907321111186631
|View full text |Cite
|
Sign up to set email alerts
|

Reference transaction assessment

Abstract: PurposeThis paper aims to survey the published journal literature on reference transaction assessment. Its purpose is to highlight the need for a multiple perspectives approach due to the complexity of reference transactions. Satisfaction indicators, behavioral aspects, accuracy rates, success measures, and other desired transaction outcomes contribute to the need for a broader assessment picture.Design/methodology/approachThis is a review from the first decade of the twenty‐first century. Selected were papers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Reference transaction has gained attention in the library and information literature (McLaughlin, 2011;Saxton & Richardson, 2002). The concept is referred to as an information contact that involves multiple elements such as knowledge, recommendations, interpretation, or instruction in the use of information sources by library staff.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Reference transaction has gained attention in the library and information literature (McLaughlin, 2011;Saxton & Richardson, 2002). The concept is referred to as an information contact that involves multiple elements such as knowledge, recommendations, interpretation, or instruction in the use of information sources by library staff.…”
mentioning
confidence: 99%
“…computer-assisted instruction); library catalogs and other record holdings; other libraries and institutions through communication or referral; and persons both inside and outside the library. The skill needed for an effective reference transaction includes conducting interviews; matching patrons' needs to appropriate resources; teaching patrons to use and perform appropriate Internet searches; and assessing health information (McLaughlin, 2011).…”
mentioning
confidence: 99%
“…8 In a review of literature published 2001-2010, McLaughlin observed that the library assessment literature lacked a "universally accepted set of standard approaches, study methodologies, and reporting formats for comparison and analysis" of the outcome of reference transactions. 9 At the 2015 ACRL Conference, Savage made a similar observation, suggesting our profession is "inattentive" to assessment of librarian-patron interactions at the reference desk or in other consultative environments. 10 In various studies at large and small institutions, students who have completed a reference consultation have responded to surveys or interview questions about the consultation experience.…”
Section: What Does the Literature Indicate?mentioning
confidence: 90%
“…However, transcript analysis is both time consuming (Mungin, 2017) and limited (Belanger et al, 2016;Rabinowitz, 2021). Much of the literature on chat reference has been case studies with limited generalizability, with McLaughlin (2011) suggesting the need for standard approaches and reporting formats across libraries.…”
Section: Introductionmentioning
confidence: 99%